Standardization of a real time PCR TaqMan assay for detection of pathogenic Leptospira sp in urine of dogs - Sedano S., André (2016)
This study aimed to standardize a TaqMan Real-Time PCR assay to detect the presence of pathogenic leptospires in urine samples of a dog infected in vitro with standard strains of Leptospira spp. Samples were obtained from a clinically healthy dog, negative to the microagglutination test. Lepto R and Lepto F primers, specific for Leptospira sp and a Lepto TaqMan probe were used, which amplified and hybridized respectively a portion of the rrs gene, differentiating between pathogenic and nonpathogenic species of Leptospira. Thermocycling program was standardized with 35 cycles of 95 °C for 15 s and 60 °C for 1 min with an initial cycle of 95 °C for 5 min. Cycle threshold (Ct) values determined during the standardization of PCR were from 12.53 to 18.21 for the 25 pathogenic strains of Leptospira sp. In contrast, saprophytic Leptospira and other species of bacteria did not produce any specific Ct value. The standard strain was detected up to a dilution of 102 with a Ct value of 29.98 at an efficiency of 1.13 and a correlation coefficient (R2) of 0.993. DNA was detected in infected urine samples from the dilution of 107 leptospires/ml with a Ct value of 17.54 to a minimum dilution of 102 leptospires/ml with a Ct value of 29.87.